Tree water storage and its diurnal dynamics related to sap flow and changes in stem volume in old-growth Douglas-fir trees - Cermák, Jan; Kucera, Jiri; Bauerle, William L; Phillips, Nathan; Hinckley, Thomas M (Tree physiology, 2007)
Diurnal and seasonal tree water storage was studied in three large Douglas-fir (Pseudotsuga menziesii [Mirb.] Franco) trees at the Wind River Canopy Crane Research site. Changes in water storage were based on measurements of sap flow and changes in stem volume and tissue water content at different heights in the stem and branches. We measured sap flow by two variants of the heat balance method (with internal heating in stems and external heating in branches), stem volume with electronic dendrometers, and tissue water content gravimetrically. Water storage was calculated from the differences in diurnal courses of sap flow at different heights and their integration. Old-growth Douglas-fir trees contained large amounts of free water: stem sapwood was the most important storage site, followed by stem phloem, branch sapwood, branch phloem and needles. There were significant time shifts (minutes to hours) between sap flow measured at different positions within the transport system (i.e., stem base to shoot tip), suggesting a highly elastic transport system. On selected fine days between late July and early October, when daily transpiration ranged from 150 to 300 liters, the quantity of stored water used daily ranged from 25 to 55 liters, i.e., about 20% of daily total sap flow. The greatest amount of this stored water came from the lower stem; however, proportionally more water was removed from the upper parts of the tree relative to their water storage capacity. In addition to lags in sap flow from one point in the hydrolic pathway to another, the withdrawal and replacement of stored water was reflected in changes in stem volume. When point-to-point lags in sap flow (minutes to hours near the top and stem base, respectively) were considered, there was a strong linear relationship between stem volume changes and transpiration. Volume changes of the whole tree were small (equivalent to 14% of the total daily use of stored water) indicating that most stored water came from the stem and from its inelastic (sapwood) tissues. Whole tree transpiration can be maintained with stored water for about a week, but it can be maintained with stored water from the upper crown alone for no more than a few hours.
Keywords: stromy; Circadian Rhythm; Plant Transpiration; Water; roční období; cirkadiánní rytmus; Plant Stems; Trees; Pseudotsuga; Seasons; stonky rostlin; transpirace rostlin; voda